2019
DOI: 10.1186/s40594-019-0170-7
|View full text |Cite
|
Sign up to set email alerts
|

How teacher talk guidance during Invention activities shapes students’ cognitive engagement and transfer

Abstract: Background: A key question in K-12 STEM education is how best to guide students as they engage in exploratory learning activities so that students develop transferable knowledge. We investigated this question in a study of teacher talk guidance of an exploratory activity called Invention. In this study, teachers worked one-on-one with students, guiding them as they attempted to invent ratio-based equations of physical science phenomena. We applied the interactive, constructive, active, and passive (ICAP) frame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 87 publications
0
18
0
1
Order By: Relevance
“…Others provided vague questions that likely left students unsure of what they were supposed to do, such as “Talk to your neighbor about this figure.” Though students in these courses worked during class, class time may not have been well spent, because the questions did not challenge students to generate their own understandings. Our approach, and other research, indicates that the ICAP framework can be useful for making finer distinctions in instructional practice (Chi and Wylie, 2014; Wiggins et al , 2017; Chase et al ., 2019). Finer distinctions in practices, such as contrasting active versus generative active-learning instruction, will be critical to investigating in more detail how teaching practices influence student success.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Others provided vague questions that likely left students unsure of what they were supposed to do, such as “Talk to your neighbor about this figure.” Though students in these courses worked during class, class time may not have been well spent, because the questions did not challenge students to generate their own understandings. Our approach, and other research, indicates that the ICAP framework can be useful for making finer distinctions in instructional practice (Chi and Wylie, 2014; Wiggins et al , 2017; Chase et al ., 2019). Finer distinctions in practices, such as contrasting active versus generative active-learning instruction, will be critical to investigating in more detail how teaching practices influence student success.…”
Section: Discussionmentioning
confidence: 74%
“…Knight and colleagues (2013) found that undergraduates who were explicitly prompted by instructors to use reasoning were more likely to have discussions containing evidence-based reasoning than students not prompted in this way. A study of middle school teachers and students similarly indicated that students were more likely to generate their own explanations and reasoning when the teacher gave a question or prompt that asked students to explain or generate new ideas or reasoning (i.e., generative prompt), compared with when the instructor asked questions probing for recall (i.e., active prompt; Chase et al , 2019). Additionally, greater use of generative prompts by teachers were associated with better student performance on questions testing their ability to transfer knowledge to novel problems (Chase et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transfer in online training is also favoured through dialogue between trainers and trainees and collaboration between trainees [14,21]. In distance learning, the tutor has the role of advising, guiding, and motivating participation, interest, and reflection through the dialogue carried out throughout learning and in follow-up activities [18].…”
Section: Design Of An E-learning Training Course Aimed Atmentioning
confidence: 99%
“…However, research findings reveal considerable variability concerning the superiority or inferiority of collaborative as compared to individual learning in view of inferencing indicators (Andrews & Rapp, 2015;Menekse & Chi, 2019;Nokes-Malach et al, 2015). Moreover, in studies which explicitly investigate learners' collaboration activities, it is frequently observed that collaborating learners often tend to restate what has already been given instead of drawing inferences (Chase et al, 2019;Chi & Menekse, 2015;Roscoe & Chi, 2007;Webb, 2013). To explain these findings, cognitive costs are proposed in terms of collaborative learning putting higher demands on the learners' cognitive resources than individual learning.…”
Section: Benefits and Costs Of Collaboration For Inferencingmentioning
confidence: 99%